Effects of lifestyle changes during the pandemic on consumer trends of home furnishing industry in Negros Occidental - Ordanza, Raniña F.; Tabligan, Coleen Pamelle B.; Yanguas, Mary Pauline E. (2022.)
The COVID-19 pandemic has greatly affected several industries and also the consumers' behavior. The home furnishing industry has experienced resonance due to the changing behavior of the consumers in the market. This research investigates the effects caused by the changing behavior of consumers to the home furnishing industry, influenced by the pandemic. In addition, other external factors that affect the purchase decisions of the consumers were studied. The research also touched on the likelihood of the developed or changed behavior to continue even after the pandemic. The purposive sampling technique was used to filter out the respondents and the survey was conducted online, with google forms. the survey was distributed to consumers who are residents of Negros Occidental and belongs to the age generations (Generation X, Millennials, and Generation Z). The gathered data were analyzed using the SPSS to arrive at a result. The analysis shows that the majority of the home furnishing consumers are from generation Z, leading the buying power in the industry, students and full-time workers, with an average monthly income of less than Php 10,481, and those who have an owned residence.. On consumer behavior, the degree of agreement r disagreement with the statement [ i want to show my personalty in my house] before and during the pandemic is the same. Moreover, the amount of agreement or disagreement with the frequency of altering and adding decorations in home/personal space contributes statistically substantially to the model among the five assertions regarding consumer lifestyle before the pandemic, while along with other assertions regarding consumer lifestyle, the amount of agreement or disagreement about the frequency of altering and adding decorations in home/personal space no longer has a significant association with interest during the pandemic. The external factors that greatly influenced the purchase decisions of consumers is "personality", having "advertisement" to be the least influential. Moreover, factors such as the quality, price, and income are highly important in the decision making process of consumers. lastly, the likelihood of maintaining consumer behavior and interest in home furnishing products is highly possible; however, their experience and satisfaction as a home furnishing consumer during the pandemic had minimal to no effect on their consideration for repurchase after the pandemic. These results acquired would be a significant knowledge and input for the improvement of brand image, marketing strategy, and growing consumers' desire for home furnishing products.
Thesis (BSBA-Marketing). -- [Iloilo City] : University of the Philippines Visayas - College of Management, June 2022.